Insulin resistance surrogates are associated with all-cause mortality and cardiovascular mortality in population with metabolic syndrome: a retrospective cohort study of NHANES - Jinhao Liao; Linjie Wang; Lian Duan; Fengying Gong; Huijuan Zhu; Hui Pan; Hongbo Yang (Scientific Reports)
Abstract The study aimed to assess the association of five insulin resistance surrogates, namely HOMA-β (Homeostasis Model Assessment of Beta-cell Function), QUICKI (Quantitative Insulin Sensitivity Check Index), IGR (Insulin Glucose Ratio), e-IS (Estimated Insulin Sensitivity), and Bennett ISI(Bennett’s insulin sensitivity index) with all-cause and cardiovascular mortality in respondents with metabolic syndrome(MetS). The prospective cohort of 6662 participants aged 18 years and older with metabolic syndrome was extracted from the National Health and Nutrition Examination Survey(NHANES 1999–2016). The multivariate Cox proportional hazards regression model, Kaplan-Meier survival curve, and log-rank tests were applied to determine the association between the five indices and all-cause mortality and cardiovascular mortality in the MetS population. Restricted cubic splines, a two-piece segmented Cox proportional hazards model, and threshold effect analyses were performed to evaluate the nonlinear relationship. Sensitivity analyses were then conducted by removing individuals with CKD, CHF, CAD, stroke, or cancer, respectively. All five insulin resistance (IR) surrogates displayed a negative association with all-cause and cardiovascular mortality in participants with metabolic syndrome. Restricted cubic spline curves showed QUICKI, IGR, and e-IS had a nonlinear relationship with statistical significance. MetS population at the highest quartile of HOMA-β or IGR exhibited lower all-cause and cardiovascular event probabilities compared with those at the lowest quartile, and e-IS had a similar correlation with cardiovascular events. Threshold effect analyses showed that there were inflection points of IGR for all-cause and cardiovascular mortality. As IGR gradually approached inflection points, the two types of mortality risks descended by 15%[HR 0.85(0.80,0.91)] and 19%[HR 0.81(0.71,0.92)], respectively. Sensitivity analysis indicated most results were robust, but Bennett ISI did not exhibit significant outcomes in participants without CKD. Our study provides evidence that HOMA-β, QUICKI, IGR, e-IS, and Bennett ISI displayed a reverse correlation with all-cause mortality and cardiovascular mortality in participants with metabolic syndrome. The five IR surrogates should be given more attention during the follow-up of MetS population.